Methicillin-Resistant Staphylococcus aureus: Molecular Characterization, Evolution, and Epidemiology - Lakhundi, Sahreena; Zhang, Kunyan (Clinical microbiology reviews, 2018)
, a major human pathogen, has a collection of virulence factors and the ability to acquire resistance to most antibiotics. This ability is further augmented by constant emergence of new clones, making a "superbug." Clinical use of methicillin has led to the appearance of methicillin-resistant (MRSA). The past few decades have witnessed the existence of new MRSA clones. Unlike traditional MRSA residing in hospitals, the new clones can invade community settings and infect people without predisposing risk factors. This evolution continues with the buildup of the MRSA reservoir in companion and food animals. This review focuses on imparting a better understanding of MRSA evolution and its molecular characterization and epidemiology. We first describe the origin of MRSA, with emphasis on the diverse nature of staphylococcal cassette chromosome (SCC ). and its new homologues ( , , and ), SCC types (13 SCC types have been discovered to date), and their classification criteria are discussed. The review then describes various typing methods applied to study the molecular epidemiology and evolutionary nature of MRSA. Starting with the historical methods and continuing to the advanced whole-genome approaches, typing of collections of MRSA has shed light on the origin, spread, and evolutionary pathways of MRSA clones.